Ni-Bi composite coatings produced by ionic co-discharge electrodeposition - Tay, S.L. (Elsevier, 2014)
Composite coatings are widely used in applications due to their excellent mechanical properties and long service life. Most recent studies have been conducted using the co-deposition of metal with oxides or ceramic particles to produce composite coatings. However, the investigation of the co-deposition of two phases is rare. In this research, composite coatings of two phases (Ni and NiBi) were synthesized by the co-ionic discharge method. Direct current was used to produce Ni and Ni-Bi composite coatings where the Ni coating was produced for comparison purposes. After adding Bi into Ni coating, a more compact coating with smoother surface was obtained. The hardness and wear resistance of the coatings were also improved due to the incorporation of Bi into the Ni coating matrix. There was no significant difference between the corrosion properties of Ni and Ni-Bi composite coatings. The levels of the corrosion current densities and corrosion potentials were in the same range. (C) 2014 Elsevier B.V. All rights reserved.